Pembuatan Aplikasi Pembelajaran Biologi Animalia untuk SMA Kelas X Berbasis Android - Jonathan, Tommy; Andjarwirawan, Justinus; Setiawan, Alexander (Jurnal Infra, 2015)
Animal biology learning application for Android is an application that displays a variety of information about the phyla that exists in animal kingdom. It is made for Android because at the time this thesis was made, Android is growing rapidly. This application is made in order to display the material about animal, and there are exercises to test the users knowledge. Currently, because many students are using Android, this application can help students to learn animal without having to carry the book.This application is also equipped with the function for downloading materials, images, and video. It is intended to help the user in the learning process. This application can also run on Android with various sizes up to phablet and tablets.Once completed, the application can display the desired material properly and itâs features can be ran properly. Minimum operating system is KitKat, also internet connection needed is stable connection. Application design is user-friendly.